Desain Media Pembelajaran Video Animasi Berbasis ICT Untuk Meningkatkan Motivasi Belajar Peserta Didik Sekolah Dasar: Design of ICT-Based Animated Video Learning Media to Improve Learning Motivation of Elementary School Students - Syofyan, Wahyudi; Suhardi, Andi; Sukarno, Sukarno (Institut Agama Islam Daruttaqwa Gresik, 2025)
This study aims to develop ICT-based learning media in the form of animated videos and test their validity, student responses, and effectiveness in increasing student learning motivation in Pancasila Education subjects at Baiturrohman Elementary School, Jember. The study used the Research and Development (R&D) method with the ADDIE model (Analyse, Design, Develop, Implement, Evaluate). The research subjects consisted of expert lecturers, class teachers, and fifth-grade students of Baiturrohman Elementary School, Jember. The research instruments were validation questionnaires, student response questionnaires, and learning outcome tests. The validation results by material, media, and language experts showed a “very valid” category with an average score of 91.2%. Student responses to animated video media reached 93.4% with a “very good” category. The effectiveness test, conducted through a comparison of pretest and posttest scores, revealed a significant increase, with an average posttest score of 84.3, surpassing the pretest score of 67.1. Thus, ICT-based learning media in the form of animated videos are feasible to use and are effective in increasing student motivation and learning outcomes in Pancasila Education learning.